A New Class of Solution Processable Pyrazino[2, 3‐g]quinoxaline Carbazole Derivative Based on D–A–D Architecture for Achieving High EQE in Yellow and White OLEDs. Issue 13 (25th April 2022) - Vishwakarma, Vinod Kumar; Nagar, Mangey Ram; Lhouvum, Neichoihoi; Jou, Jwo‐Huei; Ammathnadu Sudhakar, Achalkumar
Abstract: A new pyrazino[2, 3‐g]quinoxaline carbazole derivative with branched alkyl peripheral chains PQC‐12b with a donor–acceptor–donor nonplanar architecture is reported. PQC‐12b exhibits high molar extinction coefficients, low bandgap, bright emission behavior in solution and solid‐state, along with positive solvatochromism. PQC‐12b is used in organic light‐emitting diodes (OLEDs) either as sole emissive material or as a guest in different host materials. Amongst these different host–guest OLEDs, CBP‐based device with the optimized concentration of PQC‐12b shows maximum values for power efficacy (PEmax ) of 14.1 lm W −1, current efficacy of 26.8 cd A −1, external quantum efficiency (EQEmax ) of 8.0%, and lifetime of 5.1 h at an initial luminance of 5000 cd m −2 with a low power efficacy roll‐off and roll‐up character in current efficacy and EQE. A triplet exciton harvesting approach is employed by incorporating thermally activated delayed fluorescent emitter 4CzIPN to obtain a PEmax of 33.4 lm W −1, a CEmax of 56.3 cd A −1, an EQEmax of 15.3%, and a maximum luminance ( L max ) of 29 400 cd m −2 . Utility of the compound in solution‐processable white OLED is explored and interestingly showed a PEmax of 42.2 lm W −1, a CEmax of 40.3 cd A −1, an EQEmax of 12.0%, and L max of 24 667 cd m −2 . Abstract : A new pyrazino[2, 3‐g]quinoxaline carbazole derivative with a nonplanar donor–acceptor–donor (D‐A‐D) architecture exhibits high molar extinction coefficients, low bandgap, bright solution and solid‐state emission behavior, along with positive solvatochromism. Yellow and white host–guest organic light‐emitting diodes fabricated with this solution‐processable emitter exhibit high external quantum efficiency and bright electroluminescence along with high device operational lifetime.